2008
DOI: 10.1002/jor.20528
|View full text |Cite
|
Sign up to set email alerts
|

Comparative stability of perpendicular versus parallel double‐locking plating systems in osteoporotic comminuted distal humerus fractures

Abstract: In distal humerus fractures, the restoration of stability is important to allow early mobilization and hence more favorable functional outcomes. In this article, we compare the biomechanical stability of perpendicular and parallel locking plating systems for the internal fixation of AO Type C2 distal humerus fractures in osteoporotic bone. Fractures were simulated in paired cadaveric bones and fixed using either the perpendicular 3.5 mm LCP distal humerus plating system (Synthes; Sydney, Australia) or the para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 28 publications
(65 reference statements)
1
79
2
3
Order By: Relevance
“…[35][36][37][38][39][40] Several biomechanical studies have demonstrated that parallel plate configurations at 180° to each other are biomechanically superior to perpendicular plates when a gap model is used to simulate fracture comminution. [43][44][45] Two clinical level IV studies have reported on the results of locked plating of distal humerus fractures (n = 52 patients). 46,47 Pooled analysis showed good/excellent results in 79% of patients, with only a single case of implant failure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[35][36][37][38][39][40] Several biomechanical studies have demonstrated that parallel plate configurations at 180° to each other are biomechanically superior to perpendicular plates when a gap model is used to simulate fracture comminution. [43][44][45] Two clinical level IV studies have reported on the results of locked plating of distal humerus fractures (n = 52 patients). 46,47 Pooled analysis showed good/excellent results in 79% of patients, with only a single case of implant failure.…”
Section: Resultsmentioning
confidence: 99%
“…Level II • 1 study 27 Level III • 2 studies 28,29 Level IV • 20 studies [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] occurs following operative intervention for distal humerus fractures.…”
Section: Quality Of the Evidencementioning
confidence: 99%
“…Self et al, 23) who demonstrated the biomechanical properties of the two systems using reconstruction plates, noted that the parallel system was stronger and stiffer. In their study of 24 humeri with simulated AO type C2 of female cadavers aged between 68 to 87 years of age using locked plates, Stoffel et al 24) demonstrated that stability was dependent on bone quality and noted that the parallel plating system was superior and showed significantly higher stability in compression and external rotation with greater ability to resist axial plastic deformation. Penzkofer et al, 25) in an artificial bone model with simulated AO/OTA type C2-3, noted that the parallel plate demonstrated the highest bending stiffness and median fatigue limit in extension, whereas in flexion, the 90-90 plating demonstrated the highest bending stiffness.…”
Section: Biomechanical Comparisonmentioning
confidence: 99%
“…There was no major difference between the performance of CL02 and CN02, and maximum torque was reached for both CL01 and CN01. [8][9][10] .…”
Section: Cadaveric Bonementioning
confidence: 99%